The permanence of the pre-hispanic patterns in the landscape of the Architecture of Pukara de San Lorenzo, Azapa Valley, Arica, s. VI-IX - Balcarce Villanueva, Esteban (2021)
This article of reflection, on the pre-Hispanic settlement of San Lorenzo (500 A.D. and 950 A.D.), located in the lower sector of the coastal desert Valley of Azapa, in Arica- Chile, in which evidence of Tiwanaku influences. It is postulated that there was a preHispanic planning process in it, which was maintaining architectures from other periods in the same place, in turn strongly related to the components of its natural, morphological and ecosystem landscape. A survey of different types of mortars used in their development is carried out declaring different stages of their planning. It is reviewed how the elements of the natural and cultural landscape influenced the planning of the town, in addition to the value it had in the construction of the place, an analysis is carried out based on the architectural observation of the field, reading existing cartographies, architectural surveys on the ground , and the information of the archaeological excavations that have been developed in the place with a reconstructive analytical methodology and a focus on urban landscape planning. It is concluded that the different construction processes superimposed over time, have given rise to the built landscape of the pre-Hispanic town studied, we can assume that there was a value given to the preexistence for the composition of the landscape complex, in the same way the geographical landmarks of the environment as founders in the sense and planning of the general layout.